Banking on the future of Asia and the Pacific 50 years of the Asian Development Bank. - McCawley, Peter (Asian Development Bank, 2017)
Focusing on the regions economic development, the evolution of the international development agenda, and the story of ADB itself, Banking on the Future of Asia and the Pacific raises several key questions What are the outstanding features of regional development to which ADB had to respond How has the bank grown and evolved in changing circumstances How did ADB successive leaders promote reforms while preserving continuity with the efforts of their predecessors ADB has played an important role in the transformation of Asia and the Pacific over the past 50 years. As ADB continues to evolve and adapt to the region changing development landscape, the experiences highlighted in this book can provide valuable insight on how best to serve Asia and the Pacific in the future.